A Novel LC‐MS Based Targeted Metabolomic Approach to Study the Biomarkers of Food Intake. Issue 22 (12th October 2020) - Tang, Yao; Zhu, Yingdong; Sang, Shengmin
Abstract : Scope: In this work, an integrated strategy is developed for rapid discovery, precise identification, and automated quantification for the biomarkers of food intake (BFIs) for specific food exposure using an ultra‐high‐pressure liquid chromatography‐high‐resolution mass spectrometry (MS) based targeted metabolomics approach. Methods and results: Using whole grain (WG) wheat intake as an example, the combination of paired mass distance networking and parallel reaction monitoring analysis is applied to selectively extract and identify WG metabolites in human urine samples. As a result, a total of 76 wheat phytochemical‐derived metabolites, including 17 alkylresorcinol metabolites, 20 benzoxazinoid derivatives, and 39 phenolic acid metabolites are identified. Subsequently, a MS spectral database consisting of the identified metabolites is created by mzVault. The characteristics of identified metabolites from the database are incorporated into the TraceFinder software to establish a quantification platform. Using a standardized urine sample, the authors are able to simultaneously quantify both free and conjugated (sulfate and glucuronide) WG wheat metabolites in real samples without further enzymatic hydrolysis, which is validated by using authentic standards to quantify these metabolites. Conclusion: This novel strategy opens the window to study the biomarkers of specific food intake and make it feasible to validate the BFIs in large‐scale human studies. Abstract : A targeted metabolomic approach is developed for rapid discovery, identification, and quantification of the dietary biomarkers for whole grain wheat intake. The combination of paired mass distance networking and parallel reaction monitoring is applied to extract and identify wheat metabolites, and a mass spectral database for identified metabolites is created in a platform to quantify these metabolites in real samples.